Mechanistic Insight into the Conversion of Tetrose Sugars to Novel α‐Hydroxy Acid Platform Molecules. Issue 2 (30th November 2012) - Dusselier, Michiel; Van Wouwe, Pieter; de Clippel, Filip; Dijkmans, Jan; Gammon, David W.; Sels, Bert F.
Abstract α‐Hydroxy acids (AHAs) such as lactic acid are considered platform molecules in the biorefinery concept and have high‐end applications in solvents and biodegradable polyester plastics. The synthesis of AHAs with a four‐carbon backbone structure is a recently emerging field. New biomass‐related routes towards their production could stimulate their practical use in new polyester plastics. Herein, we report the unique catalytic activity of soluble tin metal salts for converting tetroses, namely erythrulose and erythrose, into new four‐carbon‐backbone AHAs such as methyl vinylglycolate and methyl‐4‐methoxy‐2‐hydroxybutanoate. An in situ NMR study together with deuterium labeling experiments and control experiments with intermediates allowed us to propose a detailed reaction pathway.